Metformin Increases Protein Phosphatase 2A Activity in Primary Human Skeletal Muscle Cells Derived from Lean Healthy Participants - Mestareehi, Aktham; Zhang, Xiangmin; Seyoum, Berhane; Msallaty, Zaher; Mallisho, Abdullah; Burghardt, Kyle Jon; Kowluru, Anjaneyulu; Yi, Zhengping (Journal of Diabetes Research, 2021)
Context. Skeletal muscle insulin resistance is one of the primary contributors of type 2 diabetes (T2D). Metformin is the first-line drug for the treatment of T2D. The primary effects of metformin include decreasing glucose production in the liver and decreasing insulin resistance in the skeletal muscle. However, the molecular mechanism of metformin’s action in skeletal muscle is not well understood. Protein phosphatase 2A (PP2A), a major serine/threonine protein phosphatase, plays a pivotal role in cellular processes, such as signal transduction, cell proliferation, and apoptosis, and acts through dephosphorylating key signaling molecules such as AKT and AMPK. However, whether PP2A plays a role in metformin-induced insulin sensitivity improvement in human skeletal muscle cells remains to be elucidated. Objective. To investigate if PP2A plays a role in metformin-induced insulin sensitivity improvement in human skeletal muscle cells. Participants. Eight lean insulin-sensitive nondiabetic participants (4 females and 4 males; age: 21.0±1.0 years; BMI: 22.0±0.7 kg/m2; 2-hour OGTT: 97.0±6.0 mg/dl; HbA1c: 5.3±0.1%; fasting plasma glucose: 87.0±2.0 mg/dl; M value; 11.0±1.0 mg/kgBW/min). Design. A hyperinsulinemic-euglycemic clamp was performed to assess insulin sensitivity in human subjects, and skeletal muscle biopsy samples were obtained. Primary human skeletal muscle cells (shown to retain metabolic characteristics of donors) were cultured from these muscle biopsies that included 8 lean insulin-sensitive participants. Cultured cells were expanded, differentiated into myotubes, and treated with 50 μM metformin for 24 hours before harvesting. PP2Ac activity was measured by a phosphatase activity assay kit (Millipore) according to the manufacturer’s protocol. Results. The results indicated that metformin significantly increased the activity of PP2A in the myotubes for all 8 lean insulin-sensitive nondiabetic participants, and the average fold increase is 1.54±0.11 (P<0.001). Conclusions. These results provided the first evidence that metformin can activate PP2A in human skeletal muscle cells derived from lean healthy insulin-sensitive participants and may help to understand metformin’s action in skeletal muscle in humans.